2016
DOI: 10.1080/21507740.2015.1135831
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges of Simulation-Driven Big Neuroscience

Abstract: Research in neuroscience traditionally relies on rather small groups that deal with different questions on all levels of neuronal organization. Recent funding initiatives-notably the European "Human Brain Project" (HBP)-aim to promote Big Neuroscience for integrating research and unifying knowledge. This approach is characterized by two aspects: first, by many interacting researchers from various disciplines that deal with heterogeneous data and are accountable to a large public funding source; and second, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…In parallel, our findings illustrate the potential applicability of big data approaches to an increased variety of medical specialties. While branches of medicine like oncology [ 49 , 50 ], radiology [ 51 ] and clinical genetics [ 52 ] were already known to be particularly suitable for big data approaches, our review revealed a promising outlook associated with using big data in several other medical domains including neurology [ 53 , 54 ], psychiatry [ 55 ], immunology [ 56 ], nephrology [ 57 ], and geriatrics [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, our findings illustrate the potential applicability of big data approaches to an increased variety of medical specialties. While branches of medicine like oncology [ 49 , 50 ], radiology [ 51 ] and clinical genetics [ 52 ] were already known to be particularly suitable for big data approaches, our review revealed a promising outlook associated with using big data in several other medical domains including neurology [ 53 , 54 ], psychiatry [ 55 ], immunology [ 56 ], nephrology [ 57 ], and geriatrics [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fulfilling a situated manifestation of Volume, Velocity, Variety, and Veracity, the HBP has been used as an exemplar of “Big Neuroscience” and “big data” science (Wittenburg and Stehouwer, 2015; Christen et al, 2016). Given the increasingly broad spectrum of data-intensive research and the escalation of infrastructure development within the HBP, further criteria may also be met by some parts of the project.…”
Section: Ethics and Big Datamentioning
confidence: 99%
“…Multiple perspectives on the nature of big data and the potential risks and benefits of related analytics exist, and questions regarding moral, legal, or social responsibilities and issues of privacy and data protection, accountability, and ownership are inherent. Christen et al (2016) provide an outline of the ethical concerns presented by “Big Neuroscience,” highlighting the fundamental role of big data in this context, and other scholars have discussed ongoing and emergent ethical concerns in big data (Metcalf and Crawford, 2016; Mittelstadt and Floridi, 2016). However, data governance in a more general sense is infrequently linked to ethical issues, with neuroethical approaches lacking direct engagement with data governance (Farah, 2015), and data governance research neglecting ethical aspects (Nielsen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The types of ethical issues that the project encounters range from the well-described and understood (e.g., human subject protection) all the way to more speculative questions around the possibility of a brain simulation achieving the status of personhood (Lim, 2014). A first overview of the various issues that are specific to the type of work undertaken by the HBP was offered by Christen et al (2016). Evers (2017) offers an account of the contribution of neuroethics to this type of work, whereas Aicardi et al (2018b) discussed the broader questions of how ethical concerns can be reflected appropriately in this type of research.…”
Section: Dialogues About Ethics In the Hbpmentioning
confidence: 99%